PENDAMPINGAN PASTORAL GEREJA BAGI ANAK MELALUI PELAYANAN YANG RAMAH - Firman Panjaitan; Dwi Ratna Kusumaningdyah (POIMEN Jurnal Pastoral Konseling, 2024)
The background of this research is the concept of child-friendly service applied by the Lord Jesus in the Gospel of Luke 18:15-17. Until now, there are still many churches that have not implemented the concept of child-friendly ministry as applied by Jesus, which can be seen from the placement of children's ministry as a secondary (second) ministry. This form of service is clearly not a child-friendly service. Especially if it is noticed that children's service facilities are often not the same as service facilities for adults, the preparation of children's services is not well prepared so that Sunday school teacher servants only teach to meet the Sunday schedule. This is disproportionate to service to more well-prepared adults. By using a qualitative method, especially through a textual exegesis approach, this article will examine Luke 18:15-17 in order to examine the text more deeply. The results of the exegesis show what Luke means about the concept of child-friendly ministry, which is to bring children to Jesus so that they can receive touch (blessings and prayers) from Jesus and receive children with sincere love. This is the main task of the church in developing child-friendly services